A year living with SARS-CoV-2: an epidemiological overview of viral lineage circulation by whole-genome sequencing in Barcelona city (Catalonia, Spain). Issue 1 (31st December 2022) - Andrés, Cristina; Piñana, Maria; Borràs-Bermejo, Blanca; González-Sánchez, Alejandra; García-Cehic, Damir; Esperalba, Juliana; Rando, Ariadna; Zules-Oña, Ricardo-Gabriel; Campos, Carolina; Codina, Maria Gema; Blanco-Grau, Albert; Colomer-Castell, Sergi; et al.
ABSTRACT: Herein, we describe the genetic diversity of circulating SARS-CoV-2 viruses by whole-genome sequencing (WGS) in Barcelona city (Catalonia, Spain) throughout the first four pandemic waves. From weeks 11/2020–24/2021, SARS-CoV-2-positive respiratory samples were randomly selected per clinical setting (80% from primary care or 20% from the hospital), age group, and week. WGS was performed following the ARTICv3 protocol on MiSeq or NextSeq2000 Illumina platforms. Nearly complete consensus sequences were used for genetic characterization based on GISAID and PANGOLIN nomenclatures. From 2475 samples, 2166 (87%) were fully sequenced (78% from primary care and 22% from hospital settings). Multiple genetic lineages were co-circulating, but four were predominant at different periods. While B.1.5 (50.68%) and B.1.1 (32.88%) were the major lineages during the first pandemic wave, B.1.177 (66.85%) and B.1.1.7 (83.80%) were predominant during the second, third, and fourth waves, respectively. Almost all (96.4%) were carrying D614G mutation in the S protein, with additional mutations that define lineages or variants. But some mutations of concern, such as E484K from B.1.351 and P.1 lineages are currently under monitoring, together with those observed in the receptor-binding domain or N-terminal domain, such as L452R and T478K from B.1.617.2 lineage. The fact that a predominant lineage was observed in each pandemic wave suggests advantageous properties over other contemporary co-circulating variants. This genetic variability should be monitored, especially when a massive vaccination campaign is ongoing because the potential selection and emergence of novel antigenic SARS-CoV-2 strains related to immunological escapement events.